Analisis Pengaruh Co-Firing Biomassa Terhadap Kinerja Peralatan Boiler PLTU Batubara Unit 1 PT. XYZ - Yudhi Chandra Dwiaji (Journal of Applied Mechanical Engineering and Renewable Energy, 2023)
A biomass co-firing program has been put in place at power plants by PLN to support policies relating to the renewable energy mix. The extent to which continuous biomass co-firing at various generating load conditions will affect the performance of boiler equipment is unknown. The goal of this study is to ascertain the effects of ongoing biomass co-firing on the efficiency of boiler equipment under various generating load scenarios. An observational approach as well as interviewing techniques were used to collect the data. By hand, using Microsoft Excel software, the calculation value for a specific fuel consumption and net plant heat rate is found. The operating parameters of the boiler equipment performance are then compared with benchmark or commissioning data. The performance of boiler equipment (medium speed mill, boiler fan, air preheater) is unaffected by the co-firing process, and all of its parameters remain within acceptable bounds. As can be seen from the Mmdium speed mill motor and boiler fan flows, which decreased but not significantly, the performance of boiler equipment during the co-firing process is lighter. There is a decrease in boiler furnace temperature despite changes in load, and boiler equipment performance is still within limits. The average total production cost dropped from 485.324 Rp/Kwh to 484.585 Rp/Kwh with co-firing. During the course of the study, the average Net Plant Heat Rate during the co-firing process fell from 2862.85 kcal/kwh to 2866.35 kcal/kwh.